Synthesis of Sonicated Fibrin Nanoparticles that Modulate Fibrin Clot Polymerization and Enhance Angiogenic Responses - Roosa, Colleen A. (Colloids Surf B Biointerfaces, 2021)
Chronic wounds can occur when the healing process is disrupted and the wound remains in a prolonged inflammatory stage that leads to severe tissue damage and poor healing outcomes. Clinically used treatments, such as high density, FDA-approved fibrin sealants, do not provide an optimal environment for native cell proliferation and subsequent tissue regeneration. Therefore, new treatments outside the confines of these conventional fibrin bulk gel therapies are required. We have previously developed flowable, low-density fibrin nanoparticles that, when coupled to keratinocyte growth factor, promote cell migration and epithelial wound closure in vivo. Here, we report a new high throughput method for generating the fibrin nanoparticles using probe sonication, which is less time intensive than the previously reported microfluidic method, and investigate the ability of the sonicated fibrin nanoparticles (SFBN) to promote clot formation and cell migration in vitro. The SFBNs can form a fibrin gel when combined with fibrinogen in the absence of exogenous thrombin, and the polymerization rate and fiber density in these fibrin clots is tunable based on SFBN concentration. Furthermore, fibrin gels made with SFBNs support cell migration in an in vitro angiogenic sprouting assay, which is relevant for wound healing. In this report, we show that SFBNs may be a promising wound healing therapy that can be easily produced and delivered in a flowable formulation.